The importance of group factors in the delivery of group-based parenting programmes: a process evaluation of Mellow Babies - Jessica Tanner; Philip Wilson; Philip Wilson; Daniel Wight; Lucy Thompson (Frontiers Media S.A., 2024)
IntroductionThe role of the group has been largely overlooked within evaluations of group-based parenting programmes. Group contextual factors, including size and level of homogeneity, may impact on essential group processes, such as group identification and cohesion, that are necessary to activate interpersonal change mechanisms and attain programme outcomes. This process evaluation of Mellow Babies, a 14-week attachment-based group parenting programme for mothers of infants aged under 18 months, explores how group context affected mother and practitioner experiences of the programme.MethodsIn-depth interviews were conducted with fourteen mothers and three practitioners from three different Mellow Babies groups. Framework Analysis was employed to analyse data, using groups as cases within the framework matrix while preserving individual participants within each case. This allowed comparisons to be made within and between groups.ResultsFour group contextual factors impacted on the quality of programme delivery: (1) group size; (2) level of group homogeneity; (3) pre-existing relationships; and (4) personalities within the group. These contextual factors affected the hypothesised intervention mechanisms: (1) fluid progression through the stages of group development; (2) a safe, non-judgemental, contained space; (3) social identification with group; (4) group cohesion; and (5) a culture of openness, support and empowerment.DiscussionFindings have implications for future delivery and implementation of group-based parenting programmes, for example, the importance of considering group composition during programme recruitment. Practitioners may also benefit from a stronger focus on group processes and enabling group dynamics within training, supervision, and the programme manual.